Factors Affecting Infant Feeding Practices Among Women With Severe Mental Illness - Baker, Natasha; Potts, Laura; Jennings, Stacey; Trevillion, Kylee; Howard, Louise M. (Frontiers in Global Women's Health, 2021)
Background: The health benefits of breastfeeding are well-established but for mothers with severe mental illness (SMI), the decision to breastfeed can be complex. Very few prior studies have investigated the infant feeding choices of women with SMI, or the factors associated with this. Our aims were to examine antenatal infant feeding intentions and infant feeding outcomes in a cohort of women admitted for acute psychiatric care in the first postpartum year. We also aimed to examine whether demographic and clinical characteristics associated with breastfeeding were similar to those found in previous studies in the general population, including age, employment, education, BMI, mode of delivery, smoking status, and social support. Methods: This study was a mixed-methods secondary analysis of a national cohort study, ESMI-MBU (Examining the effectiveness and cost-effectiveness of perinatal mental health services). Participants had been admitted to acute care with SMI in the first postpartum year. Infant feeding outcomes were retrospectively self-reported by women during a 1-month post-discharge interview. Free-text responses to questions relating to infant feeding and experience of psychiatric services were also explored using thematic analysis. Results: 144 (66.1%) of 218 women reported breastfeeding (mix feeding and exclusive breastfeeding). Eighty five percentage of the cohort had intended to breastfeed and of these, 76.5% did so. Factors associated with breastfeeding included infant feeding intentions, employment and non-Caucasian ethnicity. Although very few women were taking psychotropic medication contraindicated for breastfeeding, over a quarter (n = 57, 26.15%) reported being advised against breastfeeding because of their medication. Women were given this advice by psychiatry practitioners (40% n = 22), maternity practitioners (32.73% n = 18) and postnatal primary care (27.27% n = 15). Most women stopped breastfeeding earlier than they had planned to as a result (81.1% n = 43). Twenty five women provided free text responses, most felt unsupported with infant feeding due to inconsistent information about medication when breastfeeding and that breastfeeding intentions were de-prioritized for mental health care. Conclusion: Women with SMI intend to breastfeed and for the majority, this intention is fulfilled. Contradictory and insufficient advice relating to breastfeeding and psychotropic medication indicates that further training is required for professionals caring for women at risk of perinatal SMI about how to manage infant feeding in this population. Further research is required to develop a more in-depth understanding of the unique infant feeding support needs of women with perinatal SMI.